Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Well,this is a homework problem.

I need to calculate the differential entropy of random variable

$X\sim f(x)=\sqrt{a^2-x^2},\quad -a<x<a$ and $0$ otherwise. Just how to calculate $$ \int_{-a}^a \sqrt{a^2-x^2}\ln(\sqrt{a^2-x^2})\,\mathrm{d}x $$ I can get the result with Mathematica,but failed to calculate it by hand.Please give me some idea.

share|improve this question
1  
Looks gross. Have you tried IBP? –  Adam Rubinson Jul 9 '12 at 16:43
    
Don't think there is an analytic way of doing this. Will give it a try anyway and see. –  Kasun Fernando Jul 9 '12 at 17:23
    
I was trying to integrate by parts. After that everything is divergent. –  Norbert Jul 9 '12 at 17:27
    
Try then integrating from $-R$ to $R$ and make $R \to a^-$... BTW, WA cannot find the antiderivative of your function.... –  N. S. Jul 9 '12 at 17:56
2  
A fair bit of manipulation yields the equivalent expression $$2a^2\left(\log\,a \int_0^{\pi/2} \cos^2 u\;\mathrm du+\int_0^{\pi/2}\cos^2 u\log (\cos\,u)\mathrm du\right)$$ though the second integral is a bit tougher to handle... –  J. M. Jul 9 '12 at 18:14

5 Answers 5

up vote 10 down vote accepted

$$ \begin{align} \int_{-a}^a\sqrt{a^2-x^2}\log(\sqrt{a^2-x^2})\,\mathrm{d}x &=a^2\int_{-1}^1\sqrt{1-x^2}\log(\sqrt{1-x^2})\,\mathrm{d}x\\ &+a^2\log(a)\int_{-1}^1\sqrt{1-x^2}\,\mathrm{d}x\\ &=a^2\int_{-\Large\frac\pi2}^{\Large\frac\pi2}\cos^2(t)\log(\cos(t))\,\mathrm{d}t\\ &+a^2\log(a)\int_{-\Large\frac\pi2}^{\Large\frac\pi2}\cos^2(t)\,\mathrm{d}t\tag{1} \end{align} $$ The standard trick is to note that $$ \int_{-\Large\frac\pi2}^{\Large\frac\pi2}\cos^2(t)\,\mathrm{d}t=\int_{-\Large\frac\pi2}^{\Large\frac\pi2}\sin^2(t)\,\mathrm{d}t\tag{2} $$ and add the left side to both sides and divide by $2$: $$ \int_{-\Large\frac\pi2}^{\Large\frac\pi2}\cos^2(t)\,\mathrm{d}t=\frac\pi2\tag{3} $$ Now it gets just a bit trickier, but not so bad. Integration by parts yields $$ \begin{align} \int_{-\Large\frac\pi2}^{\Large\frac\pi2}\cos^2(t)\log(\cos(t))\,\mathrm{d}t &=\int_{-\Large\frac\pi2}^{\Large\frac\pi2}\cos(t)\log(\cos(t))\,\mathrm{d}\sin(t)\\ &=\int_{-\Large\frac\pi2}^{\Large\frac\pi2}\sin^2(t)\log(\cos(t))+\sin^2(t)\,\mathrm{d}t\tag{4} \end{align} $$ Now adding the left hand side of $(4)$ to both sides and dividing by $2$ after applying $(2)$ and $(3)$ gives $$ \int_{-\Large\frac\pi2}^{\Large\frac\pi2}\cos^2(t)\log(\cos(t))\,\mathrm{d}t =\frac12\int_{-\Large\frac\pi2}^{\Large\frac\pi2}\log(\cos(t))\,\mathrm{d}t+\frac\pi4\tag{5} $$ Next, note that $$ \begin{align} \int_{-\Large\frac\pi2}^{\Large\frac\pi2}\log(\cos(t))\,\mathrm{d}t &=\frac12\int_{-\Large\frac\pi2}^{\Large\frac\pi2}\log(\cos^2(t))\,\mathrm{d}t\\ &=\frac12\int_{-\Large\frac\pi2}^{\Large\frac\pi2}\log(\sin^2(t))\,\mathrm{d}t\tag{6} \end{align} $$ Adding the last two parts of $(6)$ and dividing by $2$ yields $$ \begin{align} \int_{-\Large\frac\pi2}^{\Large\frac\pi2}\log(\cos(t))\,\mathrm{d}t &=\frac14\int_{-\Large\frac\pi2}^{\Large\frac\pi2}\log(\tfrac14\sin^2(2t))\,\mathrm{d}t\\ &=\frac18\int_{-\pi}^{\pi}\log(\tfrac14\sin^2(t))\,\mathrm{d}t\\ &=\frac14\int_{-\Large\frac\pi2}^{\Large\frac\pi2}\log(\tfrac14\sin^2(t))\,\mathrm{d}t\tag{7} \end{align} $$ Equating $(6)$ and $(7)$ and subtracting half of $(6)$ from both and multiplying by $2$ gives us $$ \int_{-\Large\frac\pi2}^{\Large\frac\pi2}\log(\cos(t))\,\mathrm{d}t =-\pi\log(2)\tag{8} $$ Now it's all substituting back. Plug $(8)$ into $(5)$ to get $$ \int_{-\Large\frac\pi2}^{\Large\frac\pi2}\cos^2(t)\log(\cos(t))\,\mathrm{d}t =\frac\pi4-\frac\pi2\log(2)\tag{9} $$ To finish off, plug $(3)$ and $(9)$ into $(1)$: $$ \begin{align} \int_{-a}^a\sqrt{a^2-x^2}\log(\sqrt{a^2-x^2})\,\mathrm{d}x &=a^2\left(\frac\pi4-\frac\pi2\log(2)+\frac\pi2\log(a)\right)\\ &=\pi\frac{a^2}{4}\log\left(e\frac{a^2}{4}\right)\tag{10} \end{align} $$

share|improve this answer
    
(+1) Finally, I see a new approach. Very nice! –  Norbert Jul 9 '12 at 22:15
    
@Norbert: and a new final form as well :-) –  robjohn Jul 10 '12 at 0:27
    
Amazing!Just what I want to find.(6)(7)=>(8) is so tricky,I will never think of it by myself. –  bigeast Jul 10 '12 at 1:53

For the begining $$ \int\limits_{-a}^{a}\sqrt{a^2-x^2}\log\sqrt{a^2-x^2}dx= 2\int\limits_{0}^{a}\sqrt{a^2-x^2}\log\sqrt{a^2-x^2}dx=\{x=a\sqrt{1-y^2}\}= $$ $$ 2\int\limits_{0}^{1}ay\log(ay) \frac{aydy}{\sqrt{1-y^2}}= 2a^2\int\limits_{0}^{1}\frac{y^2}{\sqrt{1-y^2}}(\log a+\log y)dy= $$ $$ 2a^2\log(a)\int\limits_{0}^{1}\frac{y^2}{\sqrt{1-y^2}}dy+2a^2\int\limits_{0}^{1}\frac{y^2\log y}{\sqrt{1-y^2}}dy= 2a^2\log (a) I(2)+2a^2 J(2)\tag{1} $$ where $$ I(p)=\int\limits_{0}^1\frac{y^p}{\sqrt{1-y^2}}dy\qquad J(p)=\int\limits_{0}^1\frac{y^p\log y}{\sqrt{1-y^2}}dy $$ Note that $$ I(p)=\int\limits_{0}^1\frac{y^p}{\sqrt{1-y^2}}dy=\{s=y^2\}= \int\limits_{0}^1\frac{s^{p/2}}{\sqrt{1-s}}\frac{ds}{2\sqrt{s}}= \frac{1}{2}\int\limits_{0}^1 s^{(p+1)/2-1}(1-s)^{1/2-1}ds= $$ $$ \frac{1}{2}B\left(\frac{1}{2},\frac{p+1}{2}\right)= \frac{1}{2}\frac{\Gamma\left(\frac{1}{2}\right)\Gamma\left(\frac{p+1}{2}\right)}{\Gamma\left(\frac{p+2}{2}\right)}= \frac{\sqrt{\pi}}{2}\frac{\Gamma\left(\frac{p+1}{2}\right)}{\Gamma\left(\frac{p+2}{2}\right)} $$ Now take $p=2$, then $$ I(2)=\frac{\sqrt{\pi}}{2}\frac{\Gamma\left(\frac{3}{2}\right)}{\Gamma(2)}= \frac{\sqrt{\pi}}{2}\frac{\sqrt{\pi}/2}{1}=\frac{\pi}{4}\tag{2} $$ Now we proceed to the second integral $$ J(p)=\int\limits_{0}^1\frac{y^p\log y}{\sqrt{1-y^2}}dt= \frac{dI}{dp}= \frac{\sqrt{\pi}}{2}\frac{d}{dp}\left(\frac{\Gamma\left(\frac{p+1}{2}\right)}{\Gamma\left(\frac{p+2}{2}\right)}\right)= \frac{\sqrt{\pi}}{4}\frac{\Gamma'\left(\frac{p+1}{2}\right)\Gamma\left(\frac{p+2}{2}\right)-\Gamma\left(\frac{p+1}{2}\right)\Gamma'\left(\frac{p+2}{2}\right)}{\Gamma\left(\frac{p+2}{2}\right)^2} $$ $$ \frac{\sqrt{\pi}}{4}\left(\frac{\Gamma\left(\frac{p+1}{2}\right)\psi^{(0)}\left(\frac{p+1}{2}\right)}{\Gamma\left(\frac{p+2}{2}\right)}-\frac{\Gamma\left(\frac{p+1}{2}\right)\psi^{(0)}\left(\frac{p+2}{2}\right)}{\Gamma\left(\frac{p+2}{2}\right)}\right)= $$ $$ \frac{\sqrt{\pi}}{4}\frac{\Gamma\left(\frac{p+1}{2}\right)}{\Gamma\left(\frac{p+2}{2}\right)}\left(\psi^{(0)}\left(\frac{p+1}{2}\right)-\psi^{(0)}\left(\frac{p+2}{2}\right)\right) $$ Now take $p=2$, then $$ J(2)=\int\limits_{0}^1\frac{y^2\log y}{\sqrt{1-y^2}}dt= \frac{\sqrt{\pi}}{4}\frac{\Gamma\left(\frac{3}{2}\right)}{\Gamma(2)}\left(\psi^{(0)}(1)-\psi^{(0)}\left(\frac{3}{2}\right)\right)= \frac{\sqrt{\pi}}{4}\frac{\sqrt{\pi}/2}{1}\left(\psi^{(0)}\left(\frac{3}{2}\right)-\psi^{(0)}(2)\right)= \frac{\pi}{2}\left(\psi^{(0)}\left(\frac{3}{2}\right)-\psi^{(0)}(2)\right) $$ Well now we need values for polygamma function. We use the following two results given in wikipedia $$ \psi^{(m)}(z)=(-1)^{m+1}m!\sum\limits_{k=0}^\infty\frac{1}{(z+k)^{m+1}}\tag{3} $$ $$ n\psi^{(0)}(n z)-n\log n=\sum\limits_{k=0}^{n-1}\psi^{(0)}\left(z+\frac{k}{n}\right)\tag{4} $$ From $(3)$ we get $$ \psi^{(0)}(1)=-\sum\limits_{k=0}^\infty\frac{1}{1+k}=-\gamma $$ $$ \psi^{(0)}(2)=-\sum\limits_{k=0}^\infty\frac{1}{2+k}=1-\sum\limits_{k=0}^\infty\frac{1}{2+k}=1-\gamma $$ From $(4)$ with $n=2$ and $z=1$ we get $$ 2\psi^{(0)}(2)-2\log 2=\psi^{(0)}(1)+\psi^{(0)}\left(\frac{3}{2}\right) $$ hence $$ \psi^{(0)}\left(\frac{3}{2}\right)=2\psi^{(0)}(2)-2\log 2-\psi^{(0)}(1) $$ Thus, $$ J(2)=\frac{\pi}{8}(2\psi^{(0)}(2)-2\log 2-\psi^{(0)}(1)-\psi^{(0)}(2))= \frac{\pi}{8}(\psi^{(0)}(2)-2\log 2-\psi^{(0)}(1))= \frac{\pi}{8}(1-\gamma-2\log 2+\gamma)= \frac{\pi}{8}(1-\log 4)= $$ Finally!!! $$ \int\limits_{-a}^{a}\sqrt{a^2-x^2}\log\sqrt{a^2-x^2}dx= 2a^2\log (a) I(2)+2a^2 J(2)= 2a^2\log (a) \frac{\pi}{4}+2a^2 \frac{\pi}{8}(1-\log 4)= \frac{\pi a^2}{4}\left(\log \frac{a^2}{4}+1\right) $$

share|improve this answer
1  
+1 for the work (and sicne "finally" made me smile :)) –  Belgi Jul 9 '12 at 20:16

This integral can be performed via differentiation under the integral sign. First note that for $|x|\leq1$ we have $\ln \sqrt{1-x^2} = \frac12\ln (1-x^2)$. Moreover, simple application of the chain rule yields $$ \frac{d}{d\alpha} (1-x^2)^\alpha = (1-x^2)^\alpha \ln(1-x^2) .$$

The remaining integral is a special case of the beta function with $x=1/2$ and $y=\alpha+1$. Thus, we have $$\int_0^1\!dx\,(1-x^2)^\alpha = \frac12\int_0^1\!dy\,y^{1/2} (1-y)^\alpha= \frac{\sqrt{\pi} \Gamma(1+\alpha)}{2 \Gamma(\frac{3}{2} + \alpha)}.$$

The original integral, we obtain by taking the derivative with respect to $\alpha$ and afterwards setting $\alpha=1/2$; $$ \begin{align}\int_{-a}^a\!dx\,\sqrt{a^2-x^2} \ln\sqrt{a^2-x^2} &=a^{2} \int_{0}^1\!dx\,\sqrt{1-x^2} [\ln a^2 + \ln(1-x^2)]\\ &= \frac{a^2 \pi \log a}{2}+ a^{2} \frac{d}{d\alpha} \int_0^1\!dx\,(1-x^2)^\alpha \Big|_{\alpha=1/2}\\ &= \frac{a^2 \pi \log a}{2}+ a^{2} \frac{d}{d\alpha} \frac{\sqrt{\pi} \Gamma(1+\alpha)}{2 \Gamma(\frac{3}{2} + \alpha)} \Big|_{\alpha=1/2} \\ &= \frac{a^2 \pi \log a}{2}+ a^{2} \frac{\Gamma(1+\alpha)}{\Gamma(3/2+\alpha)} [\psi(1+\alpha)-\psi(\tfrac{3}{2}+\alpha)]\Big|_{\alpha=1/2} \\ &=\frac{a^2 \pi \log a}{2}+ \frac{a^{2}\pi}4(1-2 \ln 2). \end{align}$$ Where we used the special values of the $\Gamma$ and the $\psi = (\log \Gamma)'$ at integer and half-integer values.

share|improve this answer
    
Nice, concise use of the Beta function (+1). –  robjohn Jul 9 '12 at 22:06
    
Short and sweet. (+1) –  user26872 Jul 9 '12 at 22:27

[Some ideas] You can rewrite it as follows: $$\int_{-a}^a \sqrt{a^2-x^2} f(x) dx$$ where $f(x)$ is the logarithm.

Note that the integral, sans $f(x)$, is simply a semicircle of radius $a$. In other words, we can write, $$\int_{-a}^a \int_0^{\sqrt{a^2-x^2}} f(x) dy dx=\int_{-a}^a \int_0^{\sqrt{a^2-x^2}} \ln{\sqrt{a^2-x^2}} dy dx$$

Edit: Found a mistake. Thinking it through. :-)

share|improve this answer

If you let $x = a\sin(\theta)$, your integral becomes $$a^2\int_{-{\pi \over 2}}^{\pi \over 2} \ln(a\cos(\theta))\cos^2(\theta)\,d\theta$$ $$= 2a^2\int_0^{\pi \over 2} \ln(a\cos(\theta))\cos^2(\theta)\,d\theta$$ $$= 2a^2\ln(a)\int_0^{\pi \over 2}\cos^2(\theta)\,d\theta + 2a^2\int_0^{\pi \over 2} \ln(\cos(\theta))\cos^2(\theta)\,d\theta$$ The first integral is standard, and we get $$={\pi a^2 \ln(a)\over 2} + 2a^2\int_0^{\pi \over 2} \ln(\cos(\theta))\cos^2(\theta)\,d\theta$$ The integral here is ${\displaystyle {d \over dn}\bigg|_{n = 2} \int_0^{\pi \over 2} \cos^n(\theta)\,d\theta}$. According to Wolfram Alpha, $$\int_0^{\pi \over 2} \cos^n(\theta)\,d\theta = {\sqrt{\pi} \over 2}{\Gamma({n +1 \over 2}) \over \Gamma({n \over 2} + 1)}$$ Taking the derivative of this and setting $n = 2$ works out to $(\sqrt{\pi}/4)(\Gamma'({3/2}) - \Gamma'(2)\Gamma(3/2))= (\sqrt{\pi}/4)(\Gamma'({3/2}) - \Gamma'(2)(\sqrt{\pi}/2))$. So plugging this in gives as your answer: $$={\pi a^2 \ln(a)\over 2} + {\sqrt{\pi}a^2 \over 2}(\Gamma'({3/2}) - \Gamma'(2){\sqrt{\pi} \over 2})$$ Using $\Gamma'(3/2) = {\sqrt{\pi} \over 2}(2 - \gamma - \ln 4)$ and $\Gamma'(2) = 1 - \gamma$, where $\gamma$ is the Euler-Mascheroni constant, this becomes $$={\pi a^2 \ln(a)\over 2} + {\sqrt{\pi}a^2 \over 2}({\sqrt{\pi} \over 2} -{\sqrt{\pi} \ln 4 \over 2})$$ $$= {\pi a^2 \ln(a)\over 2} + {\pi a^2 \over 4} -{\pi a^2 \over 4} \ln 4$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.